2014
DOI: 10.1111/mmi.12838
|View full text |Cite
|
Sign up to set email alerts
|

Of linkers and autochaperones: an unambiguous nomenclature to identify common and uncommon themes for autotransporter secretion

Abstract: Autotransporter (AT) proteins provide a diverse array of important virulence functions to Gram-negative bacterial pathogens, and have also been adapted for protein surface display applications. The “autotransporter” moniker refers to early models that depicted these proteins facilitating their own translocation across the bacterial outer membrane. Although translocation is less autonomous than originally proposed, AT protein segments upstream of the C-terminal transmembrane β-barrel have nevertheless consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 119 publications
(263 reference statements)
1
47
0
Order By: Relevance
“…This implies that longer passengers will be more difficult to secrete and may rely more on folding as a driving force. Consistent with this hypothesis, large endogenous AT passengers appear to have stricter requirements for efficient secretion than small heterologous passengers (6,51). For example, secretion of IcsA is compromised by mutations in the C-terminal end of the endogenous passenger (52), whereas substituting the entire passenger for the smaller heterologous MalE protein results in efficient secretion (43).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This implies that longer passengers will be more difficult to secrete and may rely more on folding as a driving force. Consistent with this hypothesis, large endogenous AT passengers appear to have stricter requirements for efficient secretion than small heterologous passengers (6,51). For example, secretion of IcsA is compromised by mutations in the C-terminal end of the endogenous passenger (52), whereas substituting the entire passenger for the smaller heterologous MalE protein results in efficient secretion (43).…”
Section: Discussionsupporting
confidence: 53%
“…1) Equilibrium constants for folding were set to 10 6 . This is an order of magnitude typical for the stability of many proteins and corresponds to a ⌬G of ϳϪ8 kcal mol Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the C‐terminal domains that have been crystallized to date form nearly superimposable 12‐stranded β‐barrels (Oomen et al ., ; Barnard et al ., ; van den Berg, ; Tajima et al ., ; Zhai et al ., ). The two major domains are connected by a short ‘linker’, part of which forms an α‐helical segment that is embedded inside the β‐barrel domain (Drobnak et al ., ,). In a recent survey, hidden Markov models identified > 1500 genes that likely encode autotransporters in the genomes of Proteobacteria, Chlamydiales and Fusobacteria and confirmed that the autotransporter pathway is very widespread (Celik et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, ∼ 30% of the unique AT representatives analyzed contain a PATR. This is comparable with the abundance of the Pertactin‐like (PL) region, which we found here to be ∼ 37% (slightly more than previous estimates; Drobnak et al ., ). However, the actual usage of the PATR is much higher than 30% as it is commonly present in many copies per passenger.…”
Section: Discussionmentioning
confidence: 97%